Effect of weld dilution on post-weld thermal conductivity of austenitic stainless steel clad layers. (8th August 2018) - Sowrirajan, M; Mathews, P Koshy; Vijayan, S; Amaladasan, Y
Abstract: Cladding austenitic stainless steels are trendy these days in pressure vessels to enhance surface qualities. In this work, austenitic stainless steel clad layers deposited by flux cored arc welding process on structural steel plates used in boiler construction are investigated. To facilitate this, composite clad layers are produced with 316L stainless steel deposits on low carbon structural steel plates based on the design of experiments. Results exhibit an incremental trend of thermal conductivity with respect to percentage of weld dilution. A linear mathematical relationship is established between the percentage of weld dilution and post-weld thermal conductivity of clad layers for the prediction of thermal conductivity of clad layer deposits. These results could be supportive in the fabrication industries for producing energy efficient thermal equipment.